(untitled) (Journal of Informatics Education and Research, 2024)
The study focuses on delving into the impact of mergers & acquisitions on the public Sector Bank with the focus on economic performance, cultural performance and research development environment. This aims to assess the alignment between the perspective of respondent as well as the existing literature on the premises. While analysing these premises the findings showed that there is a strong consensus among respondents regarding merger and acquisition as the developmental strategy for PSBS. It means the correlation between PSBI as well as RDE2 supports the assertion of literature on the significant impact of these on the need for growth and intensification in the R&D environment. M&A has a considerable influence on the cultural & economic Performance of PSBS. Further, it shapes the R&D landscape. The IV (RDE1, EP1, and CP2) demonstrated a strong relationship with DV which is PSB1, that meets 94.6% of requirements. All of this aligns well with the respondent’s view and literature.